Monitoring dan Evaluasi Hasil Akreditasi BAN-PDM Provinsi NTB Kabupaten Sumbawa Tahun 2024 - Sakti, Hadi Gunawan; Arzani, M. (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The National Accreditation Board for Early Childhood Education, Basic Education, and Secondary Education (BAN-PDM) has established a series of standards and procedures for accreditation activities for Early Childhood Education, Basic Education, and Secondary Education units in order to improve the quality of education in Indonesia. Therefore, the Provincial BAN-PDM has a strategic role to ensure that the implementation of accreditation in educational units in its region meets the established quality criteria. Monitoring activities for accreditation results to educational units and/or equivalent education programs are important for the Provincial BAN-PDM to carry out as a step to ensure that the assessor's performance in implementing accreditation is in accordance with the established guidelines. Monitoring activities for accreditation results are used to ensure and guarantee that the accreditation implementation process in each province runs in accordance with the established rules. The results of monitoring activities for the accreditation results of the Provincial BAN-PDM to educational units and/or equivalent education programs are: 1) monitoring of assessor performance in implementing the accreditation process in accordance with the guidelines; and 2) monitoring of the implementation of accreditation that upholds integrity values.